IDENTIFIKASI KESEHATAN TANAMAN JATI (Tectona grandisLinn. f) DI KABUPATEN BANJAR KALIMANTAN SELATAN - Rahmawati Rahmawati; Yusanto Nugroho; Eva Prihatiningtyas (Universitas Lambung Mangkurat, 2020)
Teak (Tectona grandis Linn.f) is a commercial plant and is classified as luxurious wood with a high selling price. Teak is widely used for furniture industry. Teakin Kalimantan is an introduced plant grown in a new area with different site conditions. The purpose of this study was to identify the health of teak plants (Tectona grandis Linn. F) age ± 15. The method used is based on identification according to Alexander (1996). The results showed that the identification of teak plant health classified as moderate. Based on the highest damage location in the canopy section valued 28.68%, the highest damage type of open wound valued 22.43% and the highest damage severity 30-39% (3 rd category) with percentage 45.22 %.Keywords: Teak, Location Damage, Damage Type, Damage Severity